Attitudes Towards Science and Science Teaching -- Understanding How Coursework and Practicum Affect Preservice Elementary Teachers - Scott, Elizabeth; Rosin, Victoria (My University, 2017)
The purpose of this study is to find out whether UWEC’s elementary science methods course and local in-school (practicum) placement affect university preservice teachers’ attitudes towards science and science teaching.
Color poster with text and images.
Keywords: Elementary teachers; Science education; Student teaching; Posters